Upaya dan Kendala Konselor Puskesmas dalam Perawatan Pasien Skizofrenia - Rendi Editya Darmawan; Sudiro Sudiro (Interest : Jurnal Ilmu Kesehatan, 2020)
Introduction : Schizophrenia is a severe mental disorder and chronic affecting 20 million people worldwide. Schizophrenia is characterized by impaired of language, sense of self and behaviour distortions in thinking, perception, and emotions. Some case include delusions (fixed, false beliefs) and hallucinations (hearing voices or seeing things that are not there). Schizophrenia is treatable disease with psychosocial support and medicines is effective. The role of public health service counselor is important to give psychosocial support and medicines to patient. Aim of this studi to describe efforts and constraints public health care counselor in the care of schizophrenic patients. Methods : A descriptive qualitative study with 4 informants from public health service counselor. Purposive sampling is used to selecting informants. Analize of data was carried out qualitatively. The triangulation of sources, methods, researchers, and theories is used to test validity. The study was conducted in January-November 2019, in Pilang Kenceng Village, Madiun Regency. Data collection was carried out by in-depth interviewing using guide questions. Results : The results showed that there were 6 themes in answering research objectives are submission of training, optimizing the role of the community, early detection, providing treatment, counseling and constraints. Conclution : Efforts made by counselors have not been running optimally because of the synergy and communication with the community is not going well. Contraints in efforts in the care of schizophrenic patients is support from the government that is minimum.